2013
DOI: 10.1101/gad.215376.113
|View full text |Cite
|
Sign up to set email alerts
|

Let-7 represses Nr6a1 and a mid-gestation developmental program in adult fibroblasts

Abstract: MicroRNAs (miRNAs) are critical to proliferation, differentiation, and development. Here, we characterize gene expression in murine Dicer-null adult mesenchymal stem cell lines, a fibroblast cell type. Loss of Dicer leads to derepression of let-7 targets at levels that exceed 10-fold to 100-fold with increases in transcription. Direct and indirect targets of this miRNA belong to a mid-gestation embryonic program that encompasses known oncofetal genes as well as oncogenes not previously associated with an embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 70 publications
8
53
0
Order By: Relevance
“…Overexpression of one of these miRNAs, Let-7a, in mouse embryos prevents implantation (Liu et al, 2012). Targets of Let-7a include several genes that regulate cell proliferation (Gurtan et al, 2013), consistent with the view that there is depletion of specific elements required for progression beyond the blastocyst stage.…”
Section: Rodent Facultative Modelmentioning
confidence: 73%
“…Overexpression of one of these miRNAs, Let-7a, in mouse embryos prevents implantation (Liu et al, 2012). Targets of Let-7a include several genes that regulate cell proliferation (Gurtan et al, 2013), consistent with the view that there is depletion of specific elements required for progression beyond the blastocyst stage.…”
Section: Rodent Facultative Modelmentioning
confidence: 73%
“…This highlights the complexity of regulation of systems of genes by microRNAs in relationship to cancer. For example, let-7 microRNA can act as a tumor suppressor by suppressing growth rates through repression of the RAS pathway and sets of oncofetal genes (Gurtan et al 2013), while at the same time, let-7 has oncogenic activity by promoting angiogenesis by repressing the activity of FIH1. Let-7 and miR-125 suppress FIH1, which suppresses the transcriptional activity of HIF and thus angiogenesis in response to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…When miRNAs regulate transcription factors, they can affect cellular phenotype, as demonstrated by miR-134 regulation of differentiation through interactions with mRNAs encoding Nanog and LRH1 transcription factors (Tay et al, 2008), let-7 regulation of HMGA2 (Mayr et al, 2007) or miR-145 regulation of SOX9 (Rani et al, 2013). Some studies have suggested that miRNAs preferentially target transcription factors (Lewis et al, 2003) and cause widespread changes in transcriptional activation (Gurtan et al, 2013). Additionally, miRNAs are often found within network motifs containing transcription factors, suggesting that they act alongside transcription factors to buffer gene expression (Gerstein et al, 2012; Shalgi et al, 2007; Tsang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%